Employee participation and job satisfaction in SMEs: investigating strategic exploitation and exploration as moderators. Issue 16 (6th September 2022) - Wikhamn, Wajda; Wikhamn, Björn Remneland; Fasth, Jonas
Abstract: The study introduces three forms of employee participation in decision making in SMEs (work role, HR, and strategic) and tests two competing hypotheses regarding their positive and negative relationships with one aspect of employee wellbeing, namely job satisfaction. It further explores if one internal boundary condition – firms' exploitation and exploration – moderates the three participation-satisfaction relationships. Using multilevel data collected from top managers and employees in Swedish SMEs, the results support positive connotations of participation, with work role participation having the strongest relationship with employee job satisfaction. The results additionally highlight the role of firms' explorative orientation as an internal boundary condition for the three participation-satisfaction relationships. Specifically, the positive relationships of work role and strategic participation forms with job satisfaction were stronger under high levels of exploration. Surprisingly, participation in HR issues related negatively to satisfaction under the same conditions. The study advances HRM-SME research by discussing these findings, highlighting their implications for practitioners in SMEs, and proposing avenues for future research.